Microcontroller Based Blood Irradiator (Global Journals of Research in Engineering, 2011)
Irradiation of blood and blood products by gamma rays is a proven and safe method to inhibit T- Lymphocyte Proliferation and eliminate the risk of post transfusion graft versus host disease (T-GVHD). Transfusion-associated graft-versus-host disease (TA-GVHD) is a rare, but usually fatal, complication of transfusion. The risk associated with an individual transfusion depends on the number and viability of contaminating lymphocytes, the susceptibility of the patient's immune system to their engraftment and the degree of immunological disparity between donor and patient. This paper aims to acknowledge the importance of blood irradiator.The mainstay of prevention is gamma irradiation, which inactivates T lymphocytes whilst preserving the function oother blood cells. Leucodepletion by current filtration technology is inadequate [unproven] for this purpose. Gamma irradiation of cellular blood components is the best current technology to reduce the risk of T-GVHD to the recipients as confirmed by research and therefore being widely practiced world over in hospitals and blood banks as a life saving approach to this problem. Blood is usually irradiated in standard blood bags in dedicated blood irradiators using cobalt #x2013;60 or caesium #x2013;137 radioactive source. Thus this paper aims to contribute to the development of a control system is a based system microcontroller used for controlling the various input and output devices. The unit can be installed in a room without any additional shielding.
Keywords: transfusion; disease; individual; susceptibility